POLA PEMANFAATAN RUANG DAN PRODUKTIVITAS TANAMAN PANGAN DI TEGALAN DUSUN DENGOK VI, DESA DENGOK, PLAYEN, GUNUNGKIDUL - , SIGIT PRAWOTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The impact of the Indonesian population growth lead to greater need for land. The increasing of land needs could be supported by optimizing land use. Dryland is one of optimization of land use. Dryland is agroforestri system that can be found in Dengok VI hamlet. Dryland has a considerable contribution in improving the economy of society. The purpose this research is to determine the patterns of space utilization and productivity of crops on dryland. This research was conducted in 9 dryland wich divided into 3 small dryland each was < 0,1ha, 3 medium dryland each was 0,1ha â 0,2ha, and 3 large dryland each was > 0,2ha. There is 3 method approaching the goals of this research, namely: (1) Vegetation analysis to determine density and dominance (2) Strata of vertical crown and horizontal space analysis by a spatial approachment and three-dimensional SExI-FS (3) The crop productivity analysis was based on interviews. Based on the results, tree density decreased by increasing the widht. The percentage of crown cover on the small, medium, and large dryland respectively 38.30%, 57.50%, and 19.88%. Strata of vertical crown was composed of multistrata canopy. The greatest value of vertical strata on each dryland was in strata II. Small and the large dryland crop productivity is more optimal than the medium dryland was based on the closing canopy. The intensification of farming, the influence of the land and the dominant kind of plant is the intensification of management is rarely. Small and medium dryland crop productivity dominated by rice and the large dryland dominated by cassava plants.